2001
DOI: 10.1034/j.1600-0714.2001.300305.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of human defensins and antimicrobial proteins in oral tissues

Abstract: Antimicrobial peptides and proteins are an important part of the innate host defense. In the present study, the expression profile of three human alpha-defensins, of two human beta-defensins (hBD) and of phospholipase A-2 (PLA-2) and lysozyme was determined by reverse transcription-polymerase chain reaction (RT-PCR) in 56 non-inflamed and 18 inflamed oral tissue samples and primary oral keratinocytes and fibroblasts. The transcripts for hBD-1 and -2 as well as for PLA-2 and lysozyme were found to be widely exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 15 publications
5
84
2
2
Order By: Relevance
“…One report observed HD-5 peptide at various sites in the human female genital tract and found high ng͞ml levels of HD-5 in vaginal wash material (48). Other studies have reported HD-5 expression in the testes and male urethra, as well as in breast milk and keratinocytes of the oral and airway mucosa (49)(50)(51)(52)(53). In some of these studies, HD-5 expression appeared to correlate with local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…One report observed HD-5 peptide at various sites in the human female genital tract and found high ng͞ml levels of HD-5 in vaginal wash material (48). Other studies have reported HD-5 expression in the testes and male urethra, as well as in breast milk and keratinocytes of the oral and airway mucosa (49)(50)(51)(52)(53). In some of these studies, HD-5 expression appeared to correlate with local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Human β-defensins (HBDs or DEFB) and cathelicidin LL37 are being actively used as study models for their potent ability to kill a broad spectrum of bacteria and fungi [6,7,[9][10][11][12][13], as well as to inhibit viral infections [14,15]. HBDs are expressed mostly in epithelia [11,12,[16][17][18][19][20][21][22][23][24].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The importance of the protective role played by ␤-defensins against pathogenic microorganisms in oral epithelia has been discussed by several authors (5,15,18). Moreover, a recent observation by Putsep et al on patients suffering from morbus Kostmann (24) highlights the role of antimicrobial peptides in periodontal disease.…”
mentioning
confidence: 99%